Formation of a p‐n heterojunction photocatalyst by the interfacing of graphitic carbon nitride and delafossite CuGaO2. Issue 7 (13th May 2022) - Martinez, Benjamin; Chang, Dai‐Ning; Huang, Yu‐Cheng; Dong, Chung‐Li; Chiu, Te‐Wei; Chiang, Ming‐Hsi; Kuo, Chun‐Hong
Abstract: Photocatalysts have focused on scientific endeavors for five decades already. Their ability to generate solar fuel via relatively environmentally benign processes brings promises of a future with increasingly sustainable energy production. A class of materials, heterojunction (HJ) semiconductors, have immense potential due to their versatility, stability, and cost‐effectiveness. In addition, meticulous engineering of p‐n HJ enables the apparition of an electric field at the junction, a supplementary driving force that drives the charge carriers to separate effectively upon illumination. Therefore, we combined n‐type carbon nitride with p‐type CuGaO2 to form a photo‐active p‐n HJ. Mechanistic insights being highly sought‐after, we then employed X‐ray photoelectron spectroscopy and X‐ray absorption spectroscopy as complementary and orbital‐specific techniques to probe the changes caused by interfacing CuGaO2 with g‐C3 N4 . Abstract : The CuGaO2 /g‐C3 N4 composite has been found to form a p‐n heterojunction capable of generating an increased photocurrent for water reduction, compared to its isolated components. Its activity lies in the enhanced photo‐generated charge transfer in the photo‐catalyst. Orbital hybridization possibly enable this phenomenon, as was evidence by XPS and XAS analyses.